Exposure-response relationship between ambient PM2.5 and SO2 with COPD and SAD prevalence among individuals at high risk for COPD in Yunnan Province, China: a threshold analysis - Jinliang Meng; Geyi Wen; Guoyu Ma; Ruiqi Wang; Yanyan Xu; Yunhui Zhang; Le Cai (Frontiers in Public Health, 2026)
Background Ambient air pollution is a major risk factor for chronic obstructive pulmonary disease (COPD) and small airway dysfunction (SAD). However, evidence on their nonlinear exposure-response relationships and effect thresholds remain insufficient, and most identified thresholds lack clinical relevance evaluation. This study aimed to examine the nonlinear links of PM 2.5 and SO 2 exposure with the prevalence of COPD and SAD, identify effect thresholds, and compare clinical characteristics across subgroups stratified by these threshold values. Methods A cross-sectional study was conducted in Yunnan Province from 2021 to 2022, enrolling 11,095 permanent residents aged ≥20 years via multistage random cluster sampling. High-risk individuals were screened using COPD-SQ/COPD-PS questionnaires and received standardized pulmonary function testing. COPD was diagnosed per GOLD guidelines. SAD was defined as at least two of maximal mid-expiratory flow (MMEF), forced expiratory flow at 50% of vital capacity (FEF 50 %), and forced expiratory flow at 75% of vital capacity (FEF 75 %) below 65% of predicted values. Restricted cubic spline models were used to assess nonlinear relationships and identify thresholds. Stratification analyses were performed to compare clinical symptoms and lung function between exposure groups, and random forest models were used to evaluate the importance of exposure-related factors. Results Among high-risk participants, COPD and SAD prevalence were 27.2 % and 53.6%, respectively. Significant nonlinear exposure-response relationships were observed for both PM 2.5 and SO 2 with both outcomes (all P < 0.001). The effect thresholds were identified as 21.33 μg/m 3 for PM 2.5 and 8.67 μg/m 3 for SO 2 . Among those with PM 2.5 > 21.33 μg/m 3 , the prevalence of COPD and SAD was 33.4% and 58.4%, respectively; among those with SO 2 > 8.67 μg/m 3 , the corresponding prevalence was 30.2% and 57.4% (all P < 0.05). In addition, high exposure groups had significantly higher prevalence of cough and dyspnea, as well as → poorer lung function (FEV 1 , FVC, and FEV 1 /FVC), compared with low exposure groups. Air pollution was the associated factor for both outcomes, exceeding smoking and biomass fuel exposure. Conclusion Nonlinear relationships exist between PM 2.5 /SO 2 exposure and the prevalence of COPD and SAD, with core thresholds of 21.33 μg/m 3 (PM 2.5 ) and 8.67 μg/m 3 (SO 2 ). In high-risk individuals and COPD patients, exposure above these thresholds correlates with more severe respiratory symptoms and poorer lung function, illustrating the thresholds' clinical relevance.